Eficiência energética e throughput seguros em decode-and-forward seletivo com alocação de potência distribuída - Farhat, Jamil de Araujo (2015)
We investigate the secure energy efficiency and throughput in cooperative wireless communications systems, in which a pair of legitimate users (Alice and Bob) are assisted by a relay node and the communication occurs in the presence of a passive eavesdropper (Eve). Several cooperative protocols are compared with respect to these measures and we use of an iterative and distributed algorithm, based on Dinkelbach algorithm, to allocate power between Alice and the relay. The power allocation is performed in order to increase the secure energy efficiency, measured in secure bits/J/Hz, or secure throughput, measured in secure bits/s/Hz. About the protocols, we consider the case where Alice has perfect knowledge only about the instantaneous channel state of the legitimate channel. So, we employ a Selective Decode-and-Forward (SDF) protocol, which chooses the best type of communication between Alice and Bob (direct or cooperative communication) in order to improve security. For comparison, we consider other classical cooperative schemes such as the Amplify-and-Forward (AF), the Fixed Decode-and-Forward (DF) and the Cooperative Jamming (CJ). Our results show that SDF outperforms AF, DF and CJ in most situations. However, when the transmit rate increases or when Eve is close to the legitimate nodes, CJ has a better performance.